Strawberry shortcake Bloomin' berry garden - DIC Entertainment (Firm); Twentieth Century Fox Home Entertainment, Inc. ([United States] : 20th Century Fox Home Entertainment, 2011)
It's time for garden growing fun with Strawberry and her friends as they prepare for the Spring Flower Festival! But when magical sparkles make the Berrykins grow tall and the girls shrink down small, they discover that even when they're tiny, they can make a big difference. It's gardens, giggles and girl power in these berry exciting adventures!
Bonus features: Sunshine girls dance instruction video ; DVD-ROM printable coloring pages.
Not rated.
DVD, NTSC, region 1, widescreen (1.78:1) aspect ratio, Dolby Surround.
DVD, NTSC, region 1, widescreen (1.78:1) aspect ratio, Dolby Surround.
DVD.
English or Spanish dialogue; English or Spanish subtitles. Closed-captioned.
Keywords: Strawberry Shortcake (Fictitious character) -- Juvenile films; Gardening -- Juvenile films; Children's television programs; Animated television programs; Fiction television programs; Video recordings for the hearing impaired; DVDs